2023
DOI: 10.3390/foods12102032
|View full text |Cite
|
Sign up to set email alerts
|

GA3 Treatment Delays the Deterioration of ‘Shixia’ Longan during the On-Tree Preservation and Room-Temperature Storage and Up-Regulates Antioxidants

Abstract: Gibberellic acids had been proven to improve the fruit quality and storability by delaying deterioration and maintaining the antioxidant system. In this study, the effect of GA3 spraying at different concentrations (10, 20, and 50 mg L−1) on the quality of on-tree preserved ‘Shixia’ longan was examined. Only 50 mg L−1 GA3 significantly delayed the decline of soluble solids (22.0% higher than the control) and resulted in higher total phenolics content (TPC), total flavonoid content (TFC), and phenylalanine ammo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…It is a special phenomenon, for it has rarely been found in other horticultural fruits. Although many previous studies have attempted to understand the phenomenon, the underlying mechanism is still debated [8][9][10][11][12]. Here, we showed that the "sugar receding" of lichi and longan fruits could play a role in seed vigor maintenance via sugar supply for the seeds, which could spread the seed germination risk in unpredictable dry weather.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…It is a special phenomenon, for it has rarely been found in other horticultural fruits. Although many previous studies have attempted to understand the phenomenon, the underlying mechanism is still debated [8][9][10][11][12]. Here, we showed that the "sugar receding" of lichi and longan fruits could play a role in seed vigor maintenance via sugar supply for the seeds, which could spread the seed germination risk in unpredictable dry weather.…”
Section: Discussionmentioning
confidence: 79%
“…For such a mission, maintenance of high seed vigor for a long time is a prerequisite, in particular when no photosynthate is assigned after fruit maturation. It has long been found that a phenomenon called "sugar receding" of fruits commonly occurs in litchis and longans after fruit maturation, leading to a dramatic decrease in the aril sugar contents in around a week [8][9][10][11][12]. To date, the mechanism of "sugar receding" of fruits is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its edible aril accumulates high-leveled nutritive phytochemicals such as polysaccharides, vitamin C (about 0.8 mg g −1 fresh weight), polyphenols (about 0.75 mg g −1 fresh weight), and carbohydrates (about 150 mg g −1 fresh weight), which confers it not only the unique and appealing flavor but also the bioactive effects including antitumor, immunomodulatory and antioxidant capacity [4,5]. Thus, it is widely consumed and gains popularity with the global people [6].…”
Section: Introductionmentioning
confidence: 99%